Study of the Effect of Additives that Accelerate Solidification on the Main Properties of Foam Concrete (Eurasian Research Bulletin, 2022)
Nowadays, light construction materials are widely used in the production of modern constructions and products. At a time when the demand for heat-insulating materials is increasing every year, the production of high-efficiency composite materials based on local and industrial waste can be one of the solutions to this problem. One type of these materials is foam concrete. In this article, the effect of solidification-accelerating additives on the main properties of foam concrete was studied and conclusions were drawn based on the obtained results.